1954
DOI: 10.1071/ch9540104
|View full text |Cite
|
Sign up to set email alerts
|

The chemical constituents of Himantandra species. I. The Lignins of Himantandra baccata Bail. and H. belgraveana F. Muell

Abstract: Three new lignans have been isolated from Himantandra baccata Bail. and one from H. belgraveana F. Muell. Their structures have been elucidated, two are phenyltetralins and the other two are αα?-disubstituted tetrahydrofurans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…After chromatography on a silica gel column using hexanelether (5: 1) as eluant, the main product, (+)galcatin 14, was obtained (90mg) and crystallized as prisms from methanol, mp 11 1-1 13°C. This compound showed identity in all respects with data reported for (-)galcatin (7)(8)(9)(10) …”
Section: Isoguaiacin Dimethyl Ether 11supporting
confidence: 55%
“…After chromatography on a silica gel column using hexanelether (5: 1) as eluant, the main product, (+)galcatin 14, was obtained (90mg) and crystallized as prisms from methanol, mp 11 1-1 13°C. This compound showed identity in all respects with data reported for (-)galcatin (7)(8)(9)(10) …”
Section: Isoguaiacin Dimethyl Ether 11supporting
confidence: 55%
“…These subfractions were purified by silica gel, reverse-phase silica gel, and preparative HPLC giving three new lignans (1-3), nine known lignans (4)(5)(6)(7)(8)(9)(10)(11)(12), and other known compounds. Their structures were established on the basis of electron-impact (EI)-MS, 1 H-, 13 C-NMR, distortionless enhancement by polarization transfer (DEPT), 1 H-1 H COSY, HSQC, and HMBC as well as NOESY. All molecular ion peaks were obtained in EI-MS and their molecular formulas were obtained with high-resolution (HR)-MS.…”
Section: Resultsmentioning
confidence: 99%
“…(4), 10) (Ϫ)-zuonin-A (5), 11) (ϩ)-acuminatin (6), 12) (Ϫ)-galbacin (7), 13,14) (Ϫ)-galbelgin (8), 15,16) (Ϯ)-galgravin (9), (ϩ)-veraguensin (10), [17][18][19] machilin F (11), 20) (Ϫ)machilusin (12), 21,22) L-tryptophan, pellitorineϭN-(2-methylpropyl)-2E,4E,(9C1)-2,4-decadienamide, elemicin, 1,2,4-trimethoxyphenyl-5-aldehyde, and phytol from the aerial parts of P. futokadsura. In this study, the structural elucidation of the new compounds, futokadsurin A (1), B (2), and C (3), and complete 13 C-and 1 H-NMR assignments of other neolignans were carried out using 1 H-1 H correlation spectroscopy ( 1 H-1 H COSY), heteronuclear single-quantum coherence (HSQC), 1 H-detected heteronuclear multiple-bond correlation (HMBC), and nuclear Overhauser effect spectroscopy (NOESY) experiments.…”
mentioning
confidence: 99%
“…Inspiration for the conversion of 51 into CL3 was reported by Haworth and co-workers (Scheme 6a), wherein they used an acid-mediated cyclization of bislactone 47 , which is isoelectronic with 51 , to synthesize dihydronaphthalene 48 40. Additionally, Hughes and Richie (Scheme 6b) demonstrated that galgravin ( 49 ), a CL5a natural product, undergoes rearrangement to form dihydronaphthalene 50 under acidic conditions 41. Seemingly, both 48 and 50 arise from p QM formation, Friedel–Crafts alkylation, and dehydration.…”
Section: Resultsmentioning
confidence: 99%